“Targetting the laterals”; conservative management of tooth agenesis and peg-shaped lateral incisor by minimally invasive composite restoration: a case report - Amir, Nehal (Journal of the Pakistan Medical Association, 2025)
Maxillary lateral incisors are the most vulnerable teeth to developmental dental anomalies. These teeth are often subjected to atypical, malformative defects with a prevalence of 1.6% to 4.9%. These defects may affect the tooth’s size, structure or development. Peg-shaped lateral incisors, a microdont, are a commonly encountered defect in size. Tooth agenesis, a formative developmental defect, is characterized by the failure in the formation of tooth germ. Being in a strategic position in the aesthetic zone, maxillary lateral incisors, when affected by either microdontia or tooth agenesis, can have a profound impact on dento-facial aesthetics and the self-esteem of the affected individual. Management of these dental defects by a conservative approach is the fundamental goal of minimally invasive dentistry. This case report presents a 15-year-old boy who visited the outpatient department seeking aesthetic treatment for anomalous teeth. The patient was successfully managed with a conservative approach using direct composite restorative build-up. Keywords: Tooth agenesis; Composite resins; Aesthetics; Hypodontia; Peg Laterals.